Compound electrode and preparation method and application thereof
The composite electrode with a microporous network structure addresses the challenges of complex preparation and poor performance in secondary batteries, enhancing ion and electron permeation to improve energy and power density and cycle stability.
Patent Information
- Application Number
- CN202411359053.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing secondary batteries face challenges in achieving high energy density, power density, and cycle stability due to complex electrode preparation processes and poor electrode performance, particularly in thick electrodes with tortuous structures that hinder electrolyte seepage and ion migration.
A composite electrode with a vertically arranged microporous network structure, composed of a coating containing a composite active substance, conductive agent, solvent, and binder, is prepared using a simple process involving high-energy laser treatment, optimizing the electrode's electronic conductivity and porosity through particle grading and hierarchical structure design.
The composite electrode enhances ion and electron permeation, improves energy and power density, extends cycle life, and ensures mechanical stability, making it suitable for industrial production and application in lithium/sodium ion batteries.
Smart Images

Figure CN119208512A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and more specifically to a composite electrode and a preparation method and application thereof. Background Art
[0002] The increasing demand for battery life in electric power products places higher and higher demands on battery performance. A single positive electrode material is difficult to meet the stringent requirements of electric power products for battery performance in terms of specific energy, safety, life and cost. Currently, in batteries, by increasing the thickness of the electrode, the capacity of the battery can be increased while keeping the battery volume unchanged, which helps to develop a more compact and efficient battery system. The increase in electrode thickness can easily lead to a decrease in the utilization rate of active materials, which further leads to an increase in overpotential. At the same time, the random and dense stacking of electrode materials leads to the formation of a tortuous pore structure inside the electrode, which seriously hinders the seepage of the electrolyte, increases the ion migration distance, and makes ion migration a shortcoming of charge transfer dynamics in thick electrodes.
[0003] In the prior art, the preparation of low-tortuosity electrodes is achieved through electric field / magnetic field / temperature field induction, template method, etc., but its complicated process flow is not conducive to large-scale application. At the same time, the introduction of ion conductors in the secondary battery array electrodes still needs to be considered, and the electrons in the secondary battery are not distributed between adjacent arrays, resulting in poor electrochemical performance of the electrodes. Summary of the invention
[0004] The present invention provides a composite electrode and a preparation method and application thereof, which are used to solve the problems of complex electrode preparation process and poor electrode performance in secondary batteries in the prior art.
[0005] In the first aspect, the present invention provides a composite electrode, consisting of a coating and a current collector, wherein the effective ingredients of the coating include a composite active substance; and the coating has a vertically arranged microporous network structure; wherein the composite active substance is a combination of at least two active materials, and the active material is a positive electrode active material, or a negative electrode active material.
[0006] As a possible implementation method, the positive electrode active material includes nickel-rich layered oxides, lithium-rich layered oxides, high-pressure spinel oxides, and high-pressure polyanion compounds; the negative electrode active material includes graphite, soft carbon, graphitized carbon, silicon dioxide, silicon carbon, tin, antimony, and phosphorus.
[0007] As a possible implementation, the coating comprises the following components by mass: 40 to 90 parts of the composite active material, 3 to 20 parts of a dual-phase conductive agent, 5 to 20 parts of a solvent, and 0 to 20 parts of a binder.
[0008] As a possible implementation method, the particle size of the composite active substance is 10nm~50μm; the composite active substance is composed of particle grading between different active materials, wherein the mass ratio between any two active materials is 0.1~10:1, and the particle size ratio is 0.01~100:1; and / or the two-phase conductive agent is a conjugated system polymer material produced by a cyclization reaction of a linear polymer material.
[0009] As a possible implementation, the linear polymer material is one or a combination of several of polyethylene, polypropylene, polyvinyl chloride, polyacrylonitrile, polyester and polyvinyl alcohol; and / or the solvent is one or a combination of several of methyl pyrrolidone, N,N-dimethyl diamide, ethyl acetate, cyclopentane, dimethyl sulfoxide, acetic acid, deionized water and acetonitrile; and / or the binder is one or a combination of several of polyvinylidene fluoride, polyethylene oxide, styrene-butadiene rubber, polytetrafluoroethylene, polyacrylic acid, sodium hydroxymethyl cellulose, carboxymethyl cellulose, xanthan gum, sodium alginate, guar gum and chitosan; and / or the current collector is one of aluminum foil, copper foil, stainless steel, nickel foil and carbon foil.
[0010] As a possible implementation, the conditions of the cyclization reaction are: temperature 150-300° C., time 5-30 min.
[0011] In a second aspect, the present invention provides a method for preparing a composite electrode, comprising the following steps: uniformly mixing the raw material components according to the proportion of the formula components contained in the composite electrode described in any possible implementation method of the first aspect to obtain a coating; applying the coating on the surface of the current collector, drying it, to obtain an electrode mother sheet; and subjecting the electrode mother sheet to high-energy laser treatment to obtain the composite electrode.
[0012] As a possible implementation, the high-energy laser processing is a femtosecond laser etching processing, and the processing conditions are: wavelength of 200-1100nm, line width of 10-50μm, power of 500-2000W.
[0013] In a third aspect, the present invention provides an application of the composite electrode described in any possible implementation of the first aspect or the composite electrode prepared by the preparation method described in any possible implementation of the second aspect in a secondary battery.
[0014] In a fourth aspect, the present invention provides a secondary battery. When the active material is a positive electrode active material, the composite electrode described in any possible implementation of the first aspect or the composite electrode prepared by the preparation method described in any possible implementation of the second aspect serves as its positive electrode; and / or, when the active material is a negative electrode active material, the composite electrode described in any possible implementation of the first aspect or the composite electrode prepared by the preparation method described in any possible implementation of the second aspect serves as its negative electrode.
[0015] The composite electrode provided by the present invention can combine the advantages of components, balance and optimize the overall performance of the battery, and alleviate the volume expansion and structural stress during the charge and discharge process, thereby improving the energy density, cycle stability and service life of the battery. The composite active materials of its components are adjusted by particle grading to adjust the electrode electronic conductivity, porosity and packing density, optimize the structure and performance of the electrode, and achieve the effects of high energy density, high power density, long cycle life and high safety. In addition, the composite electrode provided by the present invention has a microstructure with a vertically arranged microporous network structure, which can realize ultrafast percolation of ions and electrons, while maintaining good interface contact and a stable electrode structure, and realizes the composite thick load, low tortuosity and mechanical stability of the electrode through the hierarchical interactive structure design.
[0016] The preparation method of the composite electrode provided by the present invention has a simple process and is suitable for industrial production. Through laser processing, vertical channels are formed in the electrode, the mass transfer capacity of the electrode is enhanced, and the electronic and ionic resistances are reduced, thereby improving the rate performance and discharge area specific capacity of the battery, especially under high rate charge and discharge conditions.
[0017] The application of the composite electrode provided by the present invention is suitable for non-water-sensitive positive and negative electrode materials of lithium / sodium ion batteries, has good scalability, and is conducive to promoting the development and utilization of ultra-high specific energy secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 SEM images of electrode A and electrode B provided in an embodiment of the present invention, wherein the left image is electrode A and the right image is electrode B.
[0020] Figure 2 This is a charge and discharge curve diagram of the button battery A provided in an embodiment of the present invention.
[0021] Figure 3 This is a charge and discharge curve diagram of the button battery B provided in an embodiment of the present invention.
[0022] Figure 4 This is a charge and discharge curve diagram of the button battery C provided in an embodiment of the present invention.
[0023] Figure 5 This is a charge and discharge curve diagram of the button battery D provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In order to solve the problems of complex electrode preparation process and poor electrode performance in secondary batteries in the prior art, an embodiment of the present invention provides a preparation experiment of a composite electrode and conducts SEM analysis. It can be found that the composite electrode provided by the present invention has a microstructure with a vertically arranged microporous network structure, which can realize ultrafast permeation of ions and electrons while maintaining good interface contact and a stable electrode structure. Through the hierarchical interactive structure design, the composite thick load, low tortuosity and mechanical stability of the electrode are achieved.
[0026] Furthermore, an embodiment of the present invention provides an experiment of a temperature field induced directional electrode structure. It can be seen that the process of temperature field induced electrode preparation includes many steps, which significantly increases the preparation cost and has a complicated process; the present invention provides a preparation method with a simple process and is suitable for industrial production.
[0027] Furthermore, the embodiment of the present invention provides a performance test of a composite electrode applied to a battery. It can be learned that it is suitable for non-water-sensitive positive and negative electrode materials of lithium / sodium ion batteries, has good expansibility, and is conducive to promoting the development and utilization of ultra-high specific energy secondary batteries. In addition, the composite electrode provided by the present invention can comprehensively combine the advantages of components, balance and optimize the overall performance of the battery, and alleviate the volume expansion and structural stress during the charge and discharge process, thereby improving the energy density, cycle stability and service life of the battery. The composite active materials of its components are adjusted through particle grading to adjust the electrode electronic conductivity, porosity and bulk density, optimize the structure and performance of the electrode, and achieve the effects of high energy density, high power density, long cycle life and high safety.
[0028] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0029] Example 1
[0030] This embodiment provides a preparation experiment of a composite electrode.
[0031] The positive electrode composite active material, linear polymer polyacrylonitrile (molecular weight 60000), solvent N-methylpyrrolidone and binder polyvinylidene fluoride are mixed uniformly in a homogenizer according to a mass ratio of 80:10:20:10 to obtain electrode coating A, wherein the positive electrode composite active material is formed by lithium-rich manganese-based oxide (particle size 100-200nm) and spinel-like phase material with a mass ratio of 1:1 and a particle size ratio of 1:10 in a ball mill; the electrode coating A is coated on the current collector aluminum foil with a coating thickness of 1mm, and after standing at room temperature for 5min, it is transferred to a drying equipment, treated at 100℃ for 8h, and then heated to 240℃ for high-temperature cyclization treatment for 30min, and then transferred to a femtosecond laser etching equipment, and treated under the conditions of a wavelength of 1030nm, a line width of 20μm, and a power of 1000W to obtain a composite electrode A.
[0032] The positive electrode composite active material was replaced with an equal mass of lithium-rich manganese-based oxide, and other conditions were the same as those for the preparation of composite electrode A to obtain composite electrode A1.
[0033] The positive electrode composite active material is replaced with the spinel-like phase material of the same mass, and other conditions are the same as those for the preparation of composite electrode A to obtain composite electrode A2.
[0034] Example 2
[0035] This embodiment provides a preparation experiment of a composite electrode.
[0036] The wavelength transferred to the femtosecond laser etching device was changed to 248 nm, and the other conditions were the same as those for the preparation of the composite electrode A, thereby obtaining the composite electrode B.
[0037] Example 3
[0038] This embodiment provides a preparation experiment of a composite electrode.
[0039] The negative electrode composite active material, linear polymer polyacrylonitrile (molecular weight 60000), solvent water and binder polyacrylic acid are mixed uniformly in a homogenizer according to a mass ratio of 80:10:20:10 to obtain an electrode coating C, wherein the negative electrode composite active material is formed by nano silicon (particle size 100-200nm) and hard carbon material with a mass ratio of 1:3 and a particle size ratio of 1:20 in a ball mill; the electrode coating C is coated on the current collector aluminum foil with a coating thickness of 1mm, and after standing at room temperature for 5min, it is transferred to a drying equipment, treated at 120℃ for 5h, and then heated to 200℃ for high-temperature cyclization treatment for 10min, and then transferred to a femtosecond laser etching equipment, and treated under the conditions of a wavelength of 1030nm, a line width of 20μm, and a power of 1000W to obtain a composite electrode C.
[0040] The negative electrode composite active material was replaced with nano-silicon of the same mass, and other conditions were the same as those for preparing the composite electrode C to obtain the composite electrode C1.
[0041] The negative electrode composite active material is replaced with the hard carbon material of the same mass, and other conditions are the same as those for preparing the composite electrode C to obtain the composite electrode C2.
[0042] Example 4
[0043] This embodiment provides a preparation experiment of a composite electrode.
[0044] The nano silicon component in the negative electrode composite active material was replaced with SiO material (particle size 3 μm), and the other conditions were the same as those for the preparation of electrode coating C to obtain electrode coating D; the electrode coating D was coated on the current collector aluminum foil with a coating thickness of 500 μm, and the other conditions were the same as those for the preparation of composite electrode C to obtain composite electrode D.
[0045] Example 5
[0046] This embodiment provides an electrode preparation experiment.
[0047] The electrode coating C prepared in Example 3 was coated on the current collector aluminum foil with a coating thickness of 30 μm. After standing at room temperature for 2 min, it was transferred to a directional freezing device and treated at a cooling rate of 0.5°C / min for 30 min. It was then treated with UV light at -25°C for 30 min (UV light wavelength 365 nm, intensity 400 mW·cm -2 ), transferred to a freeze-drying device, and treated at a pressure of 10 Pa for 15 h to obtain a composite electrode E.
[0048] Example 6
[0049] This embodiment provides an electrochemical performance test experiment of a positive electrode.
[0050] The button cell was assembled with the positive electrode to be tested as the positive electrode, the metal lithium sheet as the negative electrode, Cegrad 2500 as the separator, and the lithium ion general high-voltage positive electrode electrolyte as the electrolyte.
[0051] In this example, the composite electrodes A, A1, A2 and B prepared in Examples 1 to 2 were used as positive electrodes to be tested, and batteries A, A1, A2 and B were assembled. Charge and discharge cycles were performed at a current density of 100 mA / g in a voltage range of 2.0 to 4.8 V. The results are as follows: Figure 2 The charge and discharge curves and cycle data of batteries A, A1, A2 and B are shown in Table 1.
[0052] Table 1 Electrochemical performance test results
[0053]
[0054] As shown in Table 1, the first cycle charging capacity of battery A is 354.3mAh / g, and the first cycle discharging capacity is 343.6mAh / g. The first cycle charging capacity of button battery B is 321.1mAh / g, and the first cycle discharging capacity is 311.8mAh / g. The first cycle charging capacity of button battery A1 is 410.0mAh / g, and the first cycle discharging capacity is 405.9mAh / g; the first cycle charging capacity of button battery A2 is 306.4mAh / g, and the first cycle discharging capacity is 260.5mAh / g. It can be seen that the capacity of composite electrode A and composite electrode B in the secondary battery is between A1 and A2. Figure 1 and Figure 2 From the comparison, it can be seen that the microstructure of electrode A and electrode B changes, mainly because the change of wavelength during laser processing affects the pore width formed by laser etching, so that the pores in the longitudinal microstructure can be regulated, thereby affecting the electrode performance. At the same time, according to the cycle retention data in Table 1, it can be seen that the cycle retention of composite electrodes A and B is 95% and 93% (100 cycles), respectively, which effectively improves the cycle life of the electrode under high capacity.
[0055] Example 7
[0056] This embodiment provides an electrochemical performance test experiment of a negative electrode.
[0057] The button cell was assembled with the negative electrode to be tested as the negative electrode, the metal lithium sheet as the counter electrode, Cegrad 2500 as the separator, and the lithium ion universal negative electrode electrolyte as the electrolyte.
[0058] In this example, the composite electrodes C, C1, C2 and D prepared in Examples 3 to 4 were used as negative electrodes to be tested, respectively, button cells C, C1, C2 and D were assembled, and charge and discharge cycles were performed at a current density of 100 mA / g in a voltage range of 0.01 to 1.5 V. The results are as follows: Figure 4 And the charge and discharge curves of button batteries C, C1, C2 and D shown in Table 1.
[0059] Depend on Figure 4 As shown in Table 1, the first cycle charging capacity of button battery C is 1633.0mAh / g, and the first cycle discharge capacity is 1868.0mAh / g; the first cycle charging capacity of button battery D is 494.0mAh / g, and the first cycle discharge capacity is 513.1mAh / g. The first cycle charging capacity of button battery C1 is 3200.0mAh / g, and the first cycle discharge capacity is 3584.7mAh / g; the first cycle charging capacity of button battery C2 is 346.0mAh / g, and the first cycle discharge capacity is 368mAh / g. It can be seen that the capacity of electrode C is also between C1 and C2. Further cycle tests show that the capacity retention rate of the composite electrode at high capacity is greatly improved. At the same time, compared with battery E, although the temperature field can also induce the generation of directional pore structure, the solvent crystallization process is affected by many other factors and is difficult to accurately control, resulting in its performance and capacity retention far inferior to battery C.
[0060] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0061] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A composite electrode, characterized in that: It is composed of a coating and a current collector, wherein the effective component of the coating includes a compound active substance; and has a vertically arranged microporous network structure; Wherein, the composite active substance is a combination of at least two active materials, and the active material is a positive electrode active material or a negative electrode active material.
2. The composite electrode according to claim 1, characterized in that: The positive electrode active material includes nickel-rich layered oxides, lithium-rich layered oxides, high-pressure spinel oxides, and high-pressure polyanion compounds; The negative electrode active material includes graphite, soft carbon, graphitized carbon, silicon dioxide, silicon carbon, tin, antimony, and phosphorus.
3. The composite electrode according to claim 1, characterized in that: The coating comprises the following components by mass: 40 to 90 parts of the compound active material, 3 to 20 parts of the dual-phase conductive agent, 5 to 20 parts of the solvent and 0 to 20 parts of the binder.
4. The composite electrode according to claim 3, characterized in that: The particle size of the compound active substance is 10nm to 50μm; The composite active material is formed by particle grading of different active materials, wherein the mass ratio between any two active materials is 0.1 to 10:1, and the particle size ratio is 0.01 to 100:1; And / or, the dual-phase conductive agent is a conjugated system polymer material produced by a cyclization reaction of a linear polymer material.
5. The composite electrode according to claim 4, characterized in that: The linear polymer material is one or a combination of several of polyethylene, polypropylene, polyvinyl chloride, polyacrylonitrile, polyester and polyvinyl alcohol; And / or, the solvent is one or a combination of methyl pyrrolidone, N,N-dimethyldiamide, ethyl acetate, sulfolane, dimethyl sulfoxide, acetic acid, deionized water and acetonitrile; And / or, the binder is one or a combination of polyvinylidene fluoride, polyethylene oxide, styrene-butadiene rubber, polytetrafluoroethylene, polyacrylic acid, sodium hydroxymethyl cellulose, carboxymethyl cellulose, xanthan gum, sodium alginate, guar gum and chitosan; And / or, the current collector is one of aluminum foil, copper foil, stainless steel, nickel foil and carbon foil.
6. The composite electrode according to claim 4, characterized in that: The conditions of the cyclization reaction are: temperature 150-300° C., time 5-30 min.
7. A method for preparing a composite electrode, characterized in that: The following steps are involved: According to the formula components contained in the composite electrode according to any one of claims 1 to 6, the raw material components are mixed evenly in proportion to obtain a coating; Applying the coating on the surface of the current collector and performing drying treatment to obtain an electrode mother sheet; The electrode mother sheet is subjected to high-energy laser processing to obtain the composite electrode.
8. The preparation method according to claim 7, characterized in that: The high-energy laser treatment is a femtosecond laser etching treatment, and the treatment conditions are: a wavelength of 200 to 1100 nm, a line width of 10 to 50 μm, and a power of 500 to 2000 W.
9. Use of the composite electrode according to any one of claims 1 to 6 or the composite electrode prepared by the preparation method according to any one of claims 7 to 8 in a secondary battery.
10. A secondary battery, characterized in that: When the active material is a positive electrode active material, the composite electrode according to any one of claims 1 to 6 or the composite electrode prepared by the preparation method according to any one of claims 7 to 8 is used as the positive electrode; And / or, when the active material is a negative electrode active material, the composite electrode according to any one of claims 1 to 6 or the composite electrode prepared by the preparation method according to any one of claims 7 to 8 is used as its negative electrode.
Citation Information
Patent Citations
Negative electrode for nonaqueous secondary battery
CN101015075A
Composite material adopting conductive electron / conductive ion polymer to coat ternary positive electrode material and preparation method thereof
CN113097465A
Composite electrode plate, preparation method thereof, battery and electric equipment
CN116154099A
High-load electrode, preparation method and application
CN116885205A
Lithium-ion storage battery
US20110281143A1
